Induction of GIX antigen and gross cell surface antigen after infection by ecotropic and xenotropic murine leukemia viruses in vitro. - O'Donnell, P V (1976)
A number of ecotropic and xenotropic murine leukemia viruses were examined for their ability to induce the GIX antigen and Gross cell surface antigen (GCSA) in tissue culture fibroblasts. GIX appears to be a constituent of murine leukemia virus gp70; a molecular characterization of GCSA has not yet been reported. Antigen induction was measured by the ability of productively infected cells to absorb cytotoxic activity from the standard GIX- and GCSA-typing antisera. Cells infected by ecotropic viruses displayed four distinct phenotypes GIX:+/GCSA++, GIX-/GCSA++, GIX++/GCSA+, and GIX-/GSCA+; cells infected by xenotropic viruses were either GIX-/GCSA+ or GIX-/GCSA-. GIX induction appeared to be a type-specific property of some but not all Gross-AKR type ecotropic viruses. Differences in the degree of absorption of the GCSA antiserum by ecotropic virus- and xenotropic virus-infected cells indicated that GCSA may comprise multiple antigenic determinants.